ANALISIS PENILAIAN KINERJA KARYAWAN MENGGUNAKAN PROFILE MATCHING - Ahmad Padhil; Asih Setyo rini; A. Dwi Wahyuni P; Muhammad Fachry Hafid (JURNAL REKAYASA SISTEM INDUSTRI, 2022)
The flamboyan noodle factory is a factory that produces food in the form of noodles. This factory produces various types of noodles, namely Mie Rough (as raw material for making soup noodles, Hokkien noodles, fried noodles), Smooth Noodles (used for making dry noodles, meatball noodles etc.), Pangsit Skin (used for making dumpling crackers, martabak skin, etc.), etc) and Mie Pangsit. The make to order (MTO) production strategy is to produce according to the number of orders. This factory has four production employees and a multi-role factory owner, namely the head of the production department and the head of the procurement department. When demand increases, owners are overwhelmed in managing all these parts. Therefore, the owner wants to assess the performance of production employees for the position of head of production. The purpose of this study is to assess the performance of each production employee and choose one of the employees to be the head of production. The results of the study using the profile matching method showed that the value of the first employee was 4.83; the second employee scored 4.92; the third employee value is 4.98 and the fourth employee value is 4.94. So that the one who was chosen as the head of production was the third employee because he had the highest total score. Keywords: Performace appraisal, profile matching and method total score